2021
DOI: 10.1071/fp20144
|View full text |Cite|
|
Sign up to set email alerts
|

Ammonium metabolism in Selaginella bryopteris in response to dehydration-rehydration and characterisation of desiccation tolerant, thermostable, cytosolic glutamine synthetase from plant

Abstract: Water deficit (WD) has adverse effects on plant growth, and acclimation requires responses allowing primary metabolism to continue. Resurrection plants can serve as model system to gain insight into metabolic regulation during WD. We herein report the response of a resurrection lycophyte, Selaginella bryopteris, to dehydration-rehydration cycle with emphasis on ammonium metabolism. Dehydration of S. bryopteris fronds resulted in decrease of total protein and increase of free ammonium levels and the effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…GDH activity was determined by adding 0.1 mL enzyme solution to activate the reaction. The decreasing value in absorbance after 3 min was recorded at 340 nm (Lin and Kao 1996;Singh et al 2020).…”
Section: Measurement Of Nitrogen Assimilating Enzymes Activitymentioning
confidence: 99%
“…GDH activity was determined by adding 0.1 mL enzyme solution to activate the reaction. The decreasing value in absorbance after 3 min was recorded at 340 nm (Lin and Kao 1996;Singh et al 2020).…”
Section: Measurement Of Nitrogen Assimilating Enzymes Activitymentioning
confidence: 99%
“…The decrease in total amino acids in S. convoluta, on the other hand, differs from other resurrection plants, including Selaginella species. In these plants, total amino acids typically accumulate during dehydration (Tymms & Gaff 1978;Gaff & McGregor 1979), and function as compatible solutes or as mobile nitrogen reserves for the rehydrating tissues (Martinelli et al 2007;Yobi et al 2012Yobi et al , 2013Dinakar & Bartels 2013;Singh et al 2021).…”
Section: Chlorophyll Indexmentioning
confidence: 99%
“…According to different authors, the magnitude of proline increase can vary even for the same species. For instance, Pandey et al (2010) reported an 11-fold increase in proline levels in Selaginella bryopteris branches following desiccation, while in Singh et al (2021), this compound increased twofold after 24 h of dehydration.…”
Section: Chlorophyll Indexmentioning
confidence: 99%